Biochemical and molecular variability among Xanthomonas axonopodis pv. punicae strains, the pathogen of pomegranate bacterial blight - GIRI, MADHU S.; PRASANTHI, S.K.; KULKARNI, SRIKANTH; BENAGI, V.I.; HEGDE, YASHODA R. (Indian Phytopathology, 2011)
Bacterial blight caused by Xanthomonas axonopodis pv. punicae is the devastating disease of pomegranate. The pathogen strains were collected from different parts of Karnataka to understand the existence of biochemical and molecular diversity, if any. Among 16 strains, only 5 could hydrolyse the starch and almost all the strains produced acid from different carbon sources used in the study. Out of 16 strains, 13 produced H2S gas. The analysis of RAPD profiles showed a high level of genetic variability among the strains of X. axonopodis pv. punicae. The cluster analysis based on similarity coefficients separated the sixteen strains into two major clusters. However, result reflected that the variation exhibited by the strains of X. axonopodis pv. punicae is independent of geographical location